Response of Arabidopsis thaliana seedlings to lead exposure: effect of pre-treatment with sodium nitroprusside - Phang, Ing Chia; Leung, David W. M.; Taylor, H. Harry; Burritt, David J. (2009)
Heavy metal pollution has become a serious public health and environmental concern. The physical properties of lead (Pb), including low melting point and excellent corrosion resistance, have resulted in the extensive use of Pb. High level of Pb contamination has been reported in Tamaki Estuary, Auckland and Canterbury. These Pb contaminants are susceptible to enter human’s food chain, affecting the nervous system, kidney function and reproduction system.